The effect of Tumeric Rhizome (Curcuma Longa L) on radial arm maze and passive avoidance test in Trimethyltin-induced rat models - Sapto Yuliani; Leni Setiani (Faculty of Medicine, Universitas Islam Indonesia, 2017)
Backround : Oxidative stress can cause death of hippocampal cells associated to the deficit of learning and memory function. Turmeric rhizome contains curcuminoid which has antioxidant activity that can prevent oxidative stress, thus it was expected to prevent the deficit of learning and memory function on trimethyltin (TMT)-induced rat models. Objectve : This study aimed to determine the effect of turmeric rhizome extract on cognitive learning and memory fuction which was tested using radial arm maze and passive avoidance tests on Wistar rats injected with TMT. Methods : A total of 30 Wistar rats, male, 8-12 weeks of age were divided into 6 groups. The first (normal) group was given CMC-Na, the second (TMT) group was given CMC-Na, the third-the fifth groups were given turmeric rhizome extract (TRE) orally in the dosage of 120mg/kgBW (TRE120), 240 mg/kgBW (TRE240) and 480 mg/kgBW (TRE480), respectivelly. The sixth (P500) group was given piracetam in the dosage of 500 mg/kgBW. Treatments were given for 8 days orally. At day-9th, excluding the first group, all rats were injected with 12 mg/kgBW TMT solution intraperitoneally. One day after TMT injection, the cognitive learning and memory function was measured using radial maze and passive avoidance tests. The datas of cognitve function tests were analyzed statistically by ANOVA test followed by LSD test at significance level 0.05. Results : The results of radial maze and passive avoidance tests showed that the TRE240 group was not statistically significant different with TMT group(p>0.05). However there were significant difference between TRE120 and TMT groups, as well as between TRE480 and TMT groups (p<0.05). The administration of 480 mg/kgBW of TRE showed that its cognitive function was not significantly different with the administration of Piracetam (p>0.05). Conclusion : It can be concluded that the administration of 480 mg/kgBW of TRE can improve cognitive learning and memory function of Wistar rats injected by TMT.